2021
DOI: 10.3389/fenrg.2021.719375
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of LaNi5 and TiFe—Future Opportunities of Theoretical Research in Hydrides

Abstract: Hydrogen in the solid state compounds is still considered as a safe method of energy storage. The ultimate metal hydrides or other materials that can be used for this purpose remain unknown. Such metal hydrides shall have favorable thermodynamics and kinetics of hydrogen ad/desorption, and it shall be resistant to contamination of H2 and should not constitute any environmental hazards. Theoretical investigations, based on quantum mechanics approach, have a well-established position in modern materials research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…The (110) surface forms with the lowest energy and has an area fraction of 57.2%, suggesting that it is the most preferred orientation for the TiFe IMC. This is in agreement with a previous theoretical study, 72 the (110) peak intensification observed in X-ray diffraction (XRD), 16,73,74 and the transmission electron microscopy (TEM) analysis of TiFe lattice planes. 16,73,75 Therefore, in the following we focused on the (110) orientation as the most representative surface of TiFe.…”
Section: Resultssupporting
confidence: 93%
“…The (110) surface forms with the lowest energy and has an area fraction of 57.2%, suggesting that it is the most preferred orientation for the TiFe IMC. This is in agreement with a previous theoretical study, 72 the (110) peak intensification observed in X-ray diffraction (XRD), 16,73,74 and the transmission electron microscopy (TEM) analysis of TiFe lattice planes. 16,73,75 Therefore, in the following we focused on the (110) orientation as the most representative surface of TiFe.…”
Section: Resultssupporting
confidence: 93%